The Intermediate Role of Organizational Justice in the Relationship between Organizational Complexity and Performance Effectiveness of Human Resources - Husam Hussein Shyaa; Ali Abdulhassan Abbas (Iraqi Journal for Administrative Sciences, 2024)
This research seeks to determine the intermediate effect of organizational justice in its dimensions (distributive justice, procedural justice, interactive justice) in the relationship between the organizational complexity and performance effectiveness of human resources in their dimensions (performance quality, performance effectiveness, communication, decision making). The problem of research is that organizational complexity increases because of its vulnerability to the troubled environment, which has been reflected in its negative impact on organizational justice and the effectiveness of human resources performance. The University of Karbala was chosen as a field of research and was based on the questionnaire which included (271) academic staff. We used empirical analysis and several meta-statistics for correlation and impact analysis. They have achieved several research hypotheses. We reached several important conclusions and recommendations. One of the most important findings was the contribution of organizational justice to reducing the indirect impact of an organizational complexity on the effective performance of human resources. We showed the reasons for these results. We also recommend strengthening information justice as it contributes to reducing organizational complexity.